Prediction of Long Term Creep Behaviour of PMMA From Short Time Tests - André, José Reinas (2005)
In contrast with most previously published works, which are semi-empirical, interpolative and (limitedly) extrapolative, the model developed here enables the prediction of the non-linear creep compliance of a given amorphous or semi-crystalline polymer, providing the values of the physical parameters have been experimentally determined, for a reasonably wide range of temperature and applied stress values.